GAMBARAN SIKAP REMAJA TERHADAP PERKAWINAN USIAMUDA DI YOGYAKARTA - Sumarah, Sumarah (JURNAL MEDIA KESEHATAN, 2016)
Based on data of BPS Yogyakarta in 2013, there were 63.291 teenagers between10-19 years old, 30.862 boys and 32.429 girls. In 2012, Yogyakarta had 2.52% of earlymarriages which occurred on the teenagers below 15 years old, 2.05% on age 16, and 14.30%between 17-18 years old. Pregnancy of young age correlated with maternal mortality. One ofthe main factors causing early marriage is attitude toward early marriage itself. This studyaims are to know attitude toward early marriage.This research is descriptive quantitative. Thepopulation on this research was the teenagers between 16 – 19 years old who were present,willingly, and randomly selected to be respondents. There were 100 teenagers. The instrumentfor the data collection was a questionnaire. In data analysis process, T-score was used tomeasure attitude. Attitude toward early marriage are half positive. Most respondents havepositive attitude toward meaning, causes, and impact of early marriage. Most respondentshave negative attitude toward overcoming early marriage.